Peran Guru PAI dalam Mengatasi Degradasi Moral Siswa di SMA Takhassus Al-Qur’an Kalibeber Wonosobo - Eka Fitria Ningsih; Maryono Maryono; Salis Irvan Fuadi (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to determine the role of PAI teachers in overcoming the moral degradation of students at SMA Takhassus Al-Qur'an Kalibeber Wonosobo. Moral degradation is a phenomenon of moral decline in the character of a person or group. This study uses qualitative research methods with data collection techniques through observation, interviews and documentation. Respondents in this study were PAI teachers, school principals and students at SMA Takhassus Al-Qur'an Kalibeber Wonosobo. Data analysis techniques were carried out using the Milews and Huberman interactive model, which included data collection, data reduction, data presentation, as well as conclusions and verification. The results showed that: The role of PAI teachers in overcoming student moral degradation is going well. Supporting factors for PAI teachers in overcoming student moral degradation are: co-workers who are compact, adequate facilities and infrastructure, while the inhibiting factors are: co-workers are not compact, lack of guidance and religious education in the family, lack of self-awareness in students. The role of the PAI teacher in overcoming the moral degradation of students is classified as being effective, for example changing the attitude of students who over time have begun to comply with existing rules at school and actively participate in religious activities, although not all of them.